Manufacturing method of novel long-life antifouling material
By using raw materials such as aqueous epoxy emulsion and homemade composite anti-corrosion materials, a new long-life anti-fouling material was prepared, which solved the problem of easy corrosion of metal materials in high-salt environments and achieved good heat resistance, corrosion resistance and stickiness. The junction performance reduces the equipment maintenance cost and meets environmental protection requirements.
Patent Information
- Application Number
- CN202411561017.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
AI Technical Summary
Metal materials are easily corroded in high-salt environments, and existing anticorrosion coatings have poor anti-corrosion performance, resulting in high cost of equipment and harmful to the environment and health.
Using aqueous epoxy emulsion, zinc silicate, deionized water, additives, aqueous color paste, zinc phosphate, homemade composite anticorrosion materials and aluminum dihydrogen phosphate as raw materials, a long-life anti-fouling process is prepared by stirring and ultrasonic dispersion process. New materials.
The prepared new long-life anti-fouling materials have good heat resistance, corrosion resistance and adhesion, which can effectively delay the corrosion of metal materials in high-salt environments, reduce equipment maintenance costs, and meet environmental protection requirements.
Smart Images

Figure BDA0005117871610000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a method for manufacturing a new long-life antifouling material. Background Art
[0002] Metal materials are one of the most widely used materials due to their gloss, ductility, good electrical conductivity, heat transfer and other properties. However, metal materials often undergo varying degrees of oxidation and corrosion during processing, handling and use, which reduces the service life of metal materials or metal equipment. Metal material devices and facilities used in high-salt environments are particularly susceptible to corrosion. In order to improve the corrosion resistance of the metal material surface, chromate or phosphate metal surface treatment agents are usually used to treat the metal surface in the prior art. However, chromate is toxic to a certain extent, and the use of phosphate will produce a large amount of phosphorus-containing waste liquid. The cost of waste liquid treatment is very high. In addition, it will cause great harm to human health and the environment, and the treatment effect is poor, which does not meet the requirements of modern society for environmental protection. Another technology is to use anti-corrosion coatings on the surface of these equipment for corrosion protection. The anti-corrosion coatings in the prior art have poor anti-corrosion performance, so ships in the marine environment must go ashore and be repainted every year, and equipment and facilities in the salt environment of chemical plants must be repainted every three months, which greatly increases the use cost of equipment in high-salt environments. Based on this, the present invention proposes a new long-life anti-fouling material with good corrosion resistance, which is used to solve the problem that metal materials are easily corroded in high-salt environments. Summary of the invention
[0003] The purpose of the present invention is to provide a method for manufacturing a new long-life antifouling material to solve the problems mentioned in the above background technology.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] A method for manufacturing a new long-life antifouling material, characterized in that it comprises the following steps:
[0006] Step 1: Mix 1,5-naphthalenediamine and concentrated sulfuric acid in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 120-140°C for 8-12 hours. After the reaction is completed, add ethyl acetate to the three-necked flask for extraction, let it stand, and separate the organic layer with a separatory funnel. After the organic layer is rotated, intermediate 1 is obtained;
[0007] Step 2: Mix the intermediate 1, trifluoromethyl trifluorovinyl ether and imidazole hydrochloride in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 100-110°C for 4-6h. After the reaction is completed, rotary evaporation is performed to obtain the intermediate 2;
[0008] Step 3: Mix the intermediate 2 and dimethyl sulfoxide in a three-necked flask, start magnetic stirring, heat to dissolve the intermediate 2, then add anhydrous aluminum chloride to the three-necked flask, continue stirring for 15 minutes, and after the reaction is completed, obtain a composite anticorrosive material by silica gel column chromatography;
[0009] Step 4: Mix and stir the water-based epoxy emulsion, zinc silicate, deionized water, additives, and water-based color paste to obtain a mixed slurry;
[0010] Step 5: Add zinc phosphate, the composite anti-corrosion material obtained in the third step, and aluminum dihydrogen phosphate to the mixed slurry obtained in the fourth step, stir evenly, and then disperse by ultrasonic to obtain a new long-life antifouling material.
[0011] Furthermore, the concentrated sulfuric acid in the first step is concentrated sulfuric acid with a mass fraction of 98%.
[0012] Furthermore, the dosage ratio of 1,5-naphthalenediamine and concentrated sulfuric acid used in the first step is 0.1 mol: 60-80 mL.
[0013] Furthermore, the usage ratio of the intermediate 1, trifluoromethyl trifluorovinyl ether and imidazole hydrochloride used in the second step is 0.08 mol: 0.16-0.18 mol: 0.02-0.03 mol.
[0014] Furthermore, the usage ratio of the intermediate 2, dimethyl sulfoxide and anhydrous aluminum chloride used in the third step is 0.05 mol: 20-25 mL: 0.39-0.65 g.
[0015] Furthermore, the auxiliary agent is alkylphenol polyoxyethylene ether.
[0016] Furthermore, the water-based epoxy emulsion is an anionic water-based epoxy resin emulsion.
[0017] Furthermore, the weight proportions of the raw materials used in the fourth step are 5-10 parts of water-based epoxy emulsion, 15-20 parts of zinc silicate, 10-20 parts of deionized water, 1-3 parts of auxiliary agent, and 8-20 parts of water-based color paste.
[0018] Furthermore, the weight percentages of the raw materials used in the fifth step are 10-20 parts of zinc phosphate, 20-33 parts of the composite anti-corrosion material, and 30-40 parts of aluminum dihydrogen phosphate.
[0019] Furthermore, the time condition of ultrasonic dispersion in the fifth step is 20-30 min.
[0020] Beneficial effects of the present invention:
[0021] 1) The present invention uses water-based epoxy emulsion, zinc silicate, deionized water, additives, water-based color paste, zinc phosphate, self-made composite anti-corrosion material, and aluminum dihydrogen phosphate as raw materials to prepare a new long-life anti-fouling material. The present invention first prepares a composite anti-corrosion material, and then stirs and mixes the raw materials of water-based epoxy emulsion, zinc silicate, deionized water, additives, and water-based color paste to form a mixed slurry, and finally adds the self-made composite anti-corrosion material, zinc phosphate and aluminum dihydrogen phosphate to the mixed slurry, and then uniformly stirs and ultrasonically disperses to obtain a new long-life anti-fouling material. The preparation method of the present invention is simple and effective, has good repeatability, and is suitable for industrial production; the auxiliary agent alkylphenol polyoxyethylene ether selected in the raw material of the present invention can make the effective ingredients dispersed more evenly in the mixed slurry, and the obtained new long-life anti-fouling material has uniform components.
[0022] 2) The present invention uses 1,5-naphthalenediamine as a raw material, and obtains intermediate 1 after sulfonation with concentrated sulfuric acid. Then, intermediate 1 and trifluoromethyl trifluorovinyl ether are used as raw materials, and the amino group of intermediate 1 and the double bond of trifluoromethyl trifluorovinyl ether undergo Michael addition reaction to obtain intermediate 2. Finally, intermediate 2 and aluminum chloride undergo complex reaction to obtain a composite anti-corrosion material. The composite anti-corrosion material of the present invention is a stable aluminum complex. The naphthalene ring in the complex molecule makes the composite anti-corrosion material of the present invention have good heat resistance. The large number of carbon-fluorine bonds in the complex molecule makes the composite anti-corrosion material of the present invention have good corrosion resistance. When in use, the composite anti-corrosion material of the present invention can react with an iron metal substrate to form a stable complex layer, blocking the contact between external ions and the metal substrate, thereby achieving an anti-corrosion and anti-fouling effect.
[0023] 3) The new long-life antifouling material of the present invention has good weather resistance, good heat resistance and corrosion resistance, good adhesion, and is easy to use. The anticorrosion layer formed on the metal plate is dense and stable, not easy to decompose, and can be effective for a long time. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] A composite anti-corrosion material comprises the following preparation steps:
[0027] Step 1: Mix 0.1 mol 1,5-naphthalenediamine and 60 mL of 98% concentrated sulfuric acid in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at 120°C for 12 hours. After the reaction is completed, add ethyl acetate to the three-necked flask for extraction, let it stand, and separate the organic layer with a separatory funnel. After the organic layer is rotated, intermediate 1 is obtained;
[0028] Step 2: Mix 0.08 mol of intermediate 1, 0.16 mol of trifluoromethyl trifluorovinyl ether, and 0.02 mol of imidazole hydrochloride in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at 100°C for 6 hours. After the reaction is completed, rotary evaporation is performed to obtain intermediate 2
[0029] Step 3: Mix 0.05 mol of intermediate 2 and 20 mL of dimethyl sulfoxide in a three-necked flask, start magnetic stirring, heat to dissolve intermediate 2, then add 0.39 g of anhydrous aluminum chloride to the three-necked flask, continue stirring for 15 minutes, and after the reaction is completed, obtain a composite anti-corrosion material by silica gel column chromatography.
[0030] Example 2
[0031] A composite anti-corrosion material comprises the following preparation steps:
[0032] Step 1: Mix 0.1 mol 1,5-naphthalenediamine and 70 mL of 98% concentrated sulfuric acid in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at 130°C for 10 hours. After the reaction is completed, add ethyl acetate to the three-necked flask for extraction, let it stand, and separate the organic layer with a separatory funnel. After the organic layer is rotated, intermediate 1 is obtained;
[0033] Step 2: 0.08 mol of intermediate 1, 0.17 mol of trifluoromethyl trifluorovinyl ether, and 0.025 mol of imidazole hydrochloride were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 105°C for 5 hours. After the reaction was completed, the intermediate 2 was obtained by rotary evaporation.
[0034] Step 3: Mix 0.05 mol of intermediate 2 and 23 mL of dimethyl sulfoxide in a three-necked flask, start magnetic stirring, heat to dissolve intermediate 2, then add 0.48 g of anhydrous aluminum chloride to the three-necked flask, continue stirring for 15 minutes, and after the reaction is completed, obtain a composite anti-corrosion material by silica gel column chromatography.
[0035] Example 3
[0036] A composite anti-corrosion material comprises the following preparation steps:
[0037] Step 1: Mix 0.1 mol 1,5-naphthalenediamine and 80 mL of 98% concentrated sulfuric acid in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at 140°C for 8 hours. After the reaction is completed, add ethyl acetate to the three-necked flask for extraction, let it stand, and separate the organic layer with a separatory funnel. After the organic layer is rotated, intermediate 1 is obtained;
[0038] Step 2: Mix 0.08 mol of intermediate 1, 0.18 mol of trifluoromethyl trifluorovinyl ether, and 0.03 mol of imidazole hydrochloride in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at 110°C for 4 hours. After the reaction is completed, rotary evaporation is performed to obtain intermediate 2
[0039] Step 3: Mix 0.05 mol of intermediate 2 and 25 mL of dimethyl sulfoxide in a three-necked flask, start magnetic stirring, heat to dissolve intermediate 2, then add 0.65 g of anhydrous aluminum chloride to the three-necked flask, continue stirring for 15 minutes, and after the reaction is completed, obtain a composite anti-corrosion material by silica gel column chromatography.
[0040] Example 4
[0041] A method for manufacturing a new long-life antifouling material comprises the following steps:
[0042] Step 1: Mix and stir 5 parts of anionic waterborne epoxy resin emulsion, 15 parts of zinc silicate, 10 parts of deionized water, 1 part of alkylphenol polyoxyethylene ether, and 8 parts of waterborne color paste by weight to prepare a mixed slurry;
[0043] Step 2: Add 10 parts of zinc phosphate, 20 parts of the composite anticorrosive material obtained in Example 1 and 30 parts of aluminum dihydrogen phosphate to the mixed slurry obtained in Step 4 by weight, stir evenly and then disperse by ultrasonic for 20 minutes to obtain a new long-life antifouling material.
[0044] Example 5
[0045] A method for manufacturing a new long-life antifouling material comprises the following steps:
[0046] Step 1: Mix and stir 5 parts of anionic waterborne epoxy resin emulsion, 20 parts of zinc silicate, 10 parts of deionized water, 3 parts of alkylphenol polyoxyethylene ether, and 8 parts of waterborne color paste by weight to prepare a mixed slurry;
[0047] Step 2: Add 10 parts of zinc phosphate, 20 parts of the composite anticorrosive material obtained in Example 2, and 40 parts of aluminum dihydrogen phosphate to the mixed slurry obtained in Step 4, by weight, stir evenly, and then ultrasonically disperse for 25 minutes to obtain a new long-life antifouling material.
[0048] Example 6
[0049] A method for manufacturing a new long-life antifouling material comprises the following steps:
[0050] Step 1: by weight, 10 parts of anionic waterborne epoxy resin emulsion, 15 parts of zinc silicate, 20 parts of deionized water, 1 part of alkylphenol polyoxyethylene ether, and 20 parts of waterborne color paste are mixed and stirred to prepare a mixed slurry;
[0051] Step 2: Add 20 parts of zinc phosphate, 33 parts of the composite anticorrosive material obtained in Example 3 and 30 parts of aluminum dihydrogen phosphate to the mixed slurry obtained in Step 4, by weight, stir evenly and then disperse by ultrasonic for 30 minutes to obtain a new long-life antifouling material.
[0052] Comparative Example 1
[0053] A method for manufacturing a new long-life antifouling material comprises the following steps:
[0054] Step 1: by weight, 10 parts of anionic waterborne epoxy resin emulsion, 15 parts of zinc silicate, 20 parts of deionized water, 1 part of alkylphenol polyoxyethylene ether, and 20 parts of waterborne color paste are mixed and stirred to prepare a mixed slurry;
[0055] Step 2: Add 20 parts of zinc phosphate and 30 parts of aluminum dihydrogen phosphate to the mixed slurry obtained in step 4 by weight, stir evenly and then disperse by ultrasonic for 30 minutes to obtain a new long-life antifouling material.
[0056] Experimental Example 1
[0057] A new long-life antifouling material obtained in Examples 4-6 and Comparative Example 1 was coated on the surface of a steel material, and the steel material was immersed in a sodium chloride solution with a mass fraction of 3.5% to simulate a seawater environment. The steel material not coated with the new long-life antifouling material of the present invention was used as a blank control. The corrosion changes of the steel material in the sodium chloride solution were observed. The test results are shown in Table 1:
[0058] Table 1
[0059]
[0060] It can be seen from Table 1 that the long-life new antifouling material of the present invention in Examples 4-6 can be used for steel to effectively delay corrosion and protect the steel, while the performance of the long-life new antifouling material in Comparative Example 1 is significantly worse than that in Examples 4-6. The reason is that the composite anti-corrosion material of the present invention is not used, resulting in poor weather resistance. Combined with Table 1, it can be concluded that the long-life new antifouling material of the present invention can effectively resist fouling and corrosion on steel, and can be widely used in high-salt environments.
[0061] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for manufacturing a new long-life antifouling material, characterized in that: The following steps are involved: Step 1: Mix 1,5-naphthalenediamine and concentrated sulfuric acid in a container, stir evenly, and react at 120-140°C for 8-12h to obtain intermediate 1; Step 2: Mix intermediate 1, trifluoromethyl trifluorovinyl ether and imidazole hydrochloride in a container, stir evenly, and react at 100-110° C. for 4-6 hours to obtain intermediate 2; Step 3: Mix the intermediate 2 and dimethyl sulfoxide in a container, stir evenly, heat to dissolve the intermediate 2, then add anhydrous aluminum chloride to the container, continue stirring for 15 minutes to react to obtain a composite anticorrosive material; Step 4: Mix and stir the water-based epoxy emulsion, zinc silicate, deionized water, additives, and water-based color paste to obtain a mixed slurry; Step 5: Add zinc phosphate, the composite anti-corrosion material obtained in the third step, and aluminum dihydrogen phosphate to the mixed slurry obtained in the fourth step, stir evenly, and then disperse by ultrasonic to obtain a new long-life anti-fouling material.
2. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The concentrated sulfuric acid in the first step is concentrated sulfuric acid with a mass fraction of 98%.
3. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The amount ratio of 1,5-naphthalenediamine and concentrated sulfuric acid used in the first step is 0.1 mol: 60-80 mL.
4. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The amount ratio of the intermediate 1, trifluoromethyl trifluorovinyl ether and imidazole hydrochloride used in the second step is 0.08 mol: 0.16-0.18 mol: 0.02-0.03 mol.
5. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The usage ratio of the intermediate 2, dimethyl sulfoxide and anhydrous aluminum chloride used in the third step is 0.05 mol: 20-25 mL: 0.39-0.65 g.
6. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The auxiliary agent is alkylphenol polyoxyethylene ether.
7. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The water-based epoxy emulsion is an anionic water-based epoxy resin emulsion.
8. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The weight proportions of the raw materials used in the fourth step are 5-10 parts of water-based epoxy emulsion, 15-20 parts of zinc silicate, 10-20 parts of deionized water, 1-3 parts of auxiliary agent, and 8-20 parts of water-based color paste.
9. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The weight proportions of the raw materials used in the fifth step are 10-20 parts of zinc phosphate, 20-33 parts of the composite anticorrosive material, and 30-40 parts of aluminum dihydrogen phosphate.
10. The method for manufacturing a new long-life antifouling material according to claim 1, characterized in that: The time condition of ultrasonic dispersion in the fifth step is 20-30 minutes.